Economic contributions of international tourism receipts in Tanzania: evidence from 1990–2023 - William George (Cogent Economics & Finance, 2025)
This study investigates the economic contributions of international tourism receipts to Tanzania’s economic growth from 1990 to 2023. It seeks to determine the nature and magnitude of the relationship between tourism and GDP growth. The study employs a Vector Error Correction (VEC) model to examine both the short-run dynamics and long-run equilibrium relationship between international tourism receipts and economic growth. Time series econometric techniques, including stationarity tests, cointegration analysis, and Granger causality, are applied to evaluate the interactions over time. The empirical findings confirm the existence of a long-run equilibrium relationship, with international tourism receipts exerting a positive influence on GDP growth. Granger causality tests reveal a unidirectional causality running from tourism to economic growth. The VEC model results indicate that deviations from the long-run equilibrium are corrected at a moderate speed. This paper contributes to the literature by providing updated empirical evidence over an extended timeframe, capturing the impacts of recent global shocks such as the COVID-19 pandemic. The study’s originality lies in its long-run analytical scope and its policy relevance for leveraging tourism as a strategic driver of sustainable development, economic diversification, and resilience-building in Tanzania.